Conversion from military to civil standard of varsity WF.415 now G-APAZ and its preparation for use by Smiths aircraft instruments in accordance with the terms of M.O.S. contract 6/aircraft/14707/CB6(a) - Gover, H. W. (College of Aeronautics)
SUMMARY OF REQUIREMENTS AND BRIEF DESCRIPTIONS Varsity WF.415 was delivered as a standard aircrew training aircraft and had been in storage at No. 48 MX., Hawarden, for a considerable period. Under the contract the College was required to:- 1. Prepare the aircraft for delivery flight to Cranfield, 2. Carry out a Major Inspection. 3. Embody all outstanding modifications as required by R.T.O.Vickers. 4. Convert the aircraft from military to civil category. 5. Embody the required special modifications (listed in Part 4,Section 1). 6. Maintain the aircraft during a period of proving flights and. A,R,B. Test Flights. Prior to the delivery flight a discussion took place with the S.T.O. Hawarden. On the basis of this meeting a list of minimum requirements was raised by the Chief Inspector to fitness for flight to a one flight standard. A party of College employees was sent to prepare the aircraft, the operation taking five days. On arrival at Cranfield the aircraft underwent an acceptance check and was completely stripped. The Inspection Schedule and. Varsity Modification requirements were raised. During the period required for the design of special modifications, the Major Inspection was carried out and the standard modifications embodied. It was decided that the sections of the aircraft affected by the special modifications (mainly cabin and cockpit area) would be inspected for defects and that the major inspection would be carried out on completion of these special modifications. This ensured that the spares required in these sections would. be readily available and the major inspection, when carried out, would not uncover any serious defects. To avoid unnecessary load on the Design Department it was decided that during this period certain of the special modifications should be embodied to Flight Department drawings approved by Design The work was confined to non-structural parts. This permitted completion of a considerable number of the special modifications during overhaul, thereby releasing skilled man power for the more extensive special modifications as they were designed. During the period, close liaison was maintained with Design Department to ensure that equipment required would be available on receipt of drawings, thus avoiding, as far as possible, delay due to protracted delivery dates.